Designing Quality Management Systems For Thresher Production Using ISO 9001-2015 - Nilda Tri Putri; Azira Fitira Elsera (School of Industrial and System Engineering, Telkom University, 2018)
CV Citra Dragon is a small and medium-sized industry that produces agricultural machine tools wich is located in Padang Pariaman, West Sumatra. CV Citra Dragon has been active in production since 1976 and has the potential to increase the production of alsintan in order to compete in and outside the country. Therefore, CV Citra Dragon needs to improve the quality of the products produced. The best way to recognize the product quality is by implementing the Quality Management System (QMS). QMS of CV Citra Dragon is necessary to expand to other products which is thresher machine. The research based on ISO 9001-2015 standards. The design of QMS on CV Citra Dragon was done through field survey. Documents made on thresher production units are two compulsory and mandatory records, working procedures on thresher production, as well as working instructions and recording forms required. Once a quality document has been created, the analysis was performed by comparing the pre-existing QMS with the most recent QMS tailored to ISO 9001-2015. Therefore, some documents must be obtained by ISO 9001-2015 in accordance with the QMS used CV Citra Dragon was based on the main process approach. The results of documents that have been verified by the company are the scope of the QMS, quality policy, quality objectives, criteria for evaluation and selection of suppliers, product realization planning records, design and development records, product review, and monitoring records and measurement results. The existence of a good quality document is very important for companies to implement QMS. Keywords : Document, Quality Management System, thresher.